2015
DOI: 10.1631/jzus.a1500018
|View full text |Cite
|
Sign up to set email alerts
|

A realistic resistance deterioration model for time-dependent reliability analysis of aging bridges

Abstract: Bridge resistance and reliability may deteriorate with time due to aggressive environmental conditions and increasing road freight volumes, resulting in an increase of potential economic loss. This is thus a great concern to decision-makers managing the bridges' continued future service. Reasonable models of bridge resistance and applied loads are the fundamentals of accurate estimation/prediction of a bridge's serviceability. In this paper, a new model for resistance deterioration is proposed, which enables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…d n . Furthermore, employing the concept of "average variance" [49], the variance of Y(x) is computed as follows,…”
Section: Fitting the Variance Of Y(x)mentioning
confidence: 99%
“…d n . Furthermore, employing the concept of "average variance" [49], the variance of Y(x) is computed as follows,…”
Section: Fitting the Variance Of Y(x)mentioning
confidence: 99%
“…, t n , respectively. While the structural deterioration process is indeed a complex non-stationary stochastic process (Dieulle et al, 2003;Saassouh et al, 2007;Wang et al, 2015), neither fully-correlated nor statistically independent by nature, revealed that the assumption of fully-correlated deterioration is reasonable for reliability analysis producing acceptable error. As a result, in this study, the resistance deterioration process is assumed to be a fully-correlated one, which means that the overall trajectory of deterioration will be determined as soon as the deterioration type and the deterioration value at any time are given.…”
Section: Structural Reliability Analysismentioning
confidence: 99%
“…(4)); in such a case, G(T ) follows an inverse-lognormal distribution. (4) Some studies have also used the Gamma process to model the resistance deterioration (Dieulle et al, 2003;Wang et al, 2015), with which G(T ) follows Gamma distribution. Now, taking into account the uncertainty associated with G(T ), supposing that the PDF of G(T ) is f G (g), Eq.…”
Section: Probabilistic Model Of Resistance Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gamma process has been widely used to describe the resistance deterioration (the difference between the initial and the degraded resistances) of aging bridges (Dieulle et al 2003;Saassouh et al 2007;van Noortwijk et al 2007;Li et al 2015;Wang et al 2015;Wang et al 2019), which is, by nature, a non-decreasing process and enables the autocorrelation of the resistance deterioration process on the temporal scale to be considered. The monotonicity of a Gamma process is guaranteed by its nonnegative and independent increments.…”
Section: Introductionmentioning
confidence: 99%